Relationship of socio-economic status with nutritional status among the elderly in a rural community of Bangladesh - Debnath, Sumon Chandra (Family Medicine & Primary Care Review, 2017)
Background . A poor nutritional status is more frequent in developing and low-income countries. In these countries, the impact of socio-economic factors may be more pronounced, because of high inequities and limited access to health and social services. In the elderly population, underweight and overweight are important issues that need to be considered. Objectives . The purpose of this study was to assess the nutritional status with different socio-economic parameters among rural elderly people. Material and methods. A cross-sectional study was carried out among 330 elderly people (≥ 60 years) living in a rural community of Bangladesh. Nutritional status was assessed by the WHO referred Body Mass Index (BMI). 15 respondents were excluded from BMI measurement. Malnutrition was considered as both underweight and overweight. Results . More than half (59.7%) of the study participants were in the age group from 60 to 69 years. Females (56.1%) were predominant over males (43.9%). BMI analysis revealed that about half (48.3%) of the study participants were underweight and only 7.0% were overweight, with 44.7% being normally nourished. The prevalence of underweight was 50.0% in males and 46.9% in females; hence, overweight affected 2.1% of males and 10.9% of females. Female gender and higher age were significantly associated (p < 0.05) with the poor nutritional status of the elderly. Conclusions. This study shows a high prevalence of underweight among elderly people in rural Bangladesh. In order to reduce the proportion of the undernourished, it is important to address this subset of the population.